Brightness and uniformity measurements of plastic scintillator tiles at the CERN H2 test beam - Chatrchyan, S.; Sirunyan, A. M.; Tumasyan, A.; Litomin, A.; Mossolov, V.; Shumeiko, N.; Van de Klundert, M.; Van Haevermaet, H.; Van Mechelen, P.; Van Spilbeeck, A.; Alves, G. A.; Alda Junior, W. L.; et al. (IOP PUBLISHING LTD, 2018)
We study the light output, light collection efficiency and signal timing of a variety of organic scintillators that are being considered for the upgrade of the hadronic calorimeter of the CMS detector. The experimental data are collected at the H2 test-beam area at CERN, using a 150 GeV muon beam. In particular, we investigate the usage of over-doped and green-emitting plastic scintillators, two solutions that have not been extensively considered. We present a study of the energy distribution in plastic-scintillator tiles, the hit efficiency as a function of the hit position, and a study of the signal timing for blue and green scintillators.
Keywords: Calorimeters; Radiation-hard detectors; Scintillators and scintillating fibres and light guides; Instruments & Instrumentation